Combined mode fracture of three aluminium alloys - Oruganti Rajmohan Kashyap (2008)
The objective of this project was to evaluate the fracture resistance of three aerospace grade aluminium alloys under combined mode I - mode III loading conditions, with a view to furthering the concept of the fracture mechanism map. Slow strain rate testing was done using compact tension specimens, while impact testing was done using modified Charpy specimens. An aluminium based metal matrix composite was also tested primarily to provide a macroscopically semi-brittle material, with an aluminium matrix providing a basis for comparison with the aluminium alloys.